Montenegro : 2011 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Montenegro. (IMF Staff Country Reports; Country Report ;, 2011)
Since its independence in 2006, Montenegro has experienced an economic and financial roller coaster ride. The baseline is predicated on continued improvements in cost competitiveness and productivity-raising foreign direct investment (FDI). Avoiding a relapse into recession will thus require strengthening the health of the banking system and removing impediments to restructuring the economy. Montenegro's attractiveness to investors will depend on reducing macroeconomic and structural vulnerabilities. The business environment needs to be further improved. Redressing solvency issues and improving liquidity were jointly seen as priority tasks.